2015
DOI: 10.1002/anie.201505193
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Chemoselectivity in Visible‐Light Photoredox Catalysis: Four Diverse Aerobic Radical Cascade Reactions

Abstract: Reported is the controllable selectivity syntheses of four distinct products from the same starting materials by visible-light photoredox catalysis. By employing a dicyanopyrazine-derived chromophore (DPZ) as photoredox catalyst, an aerobic radical mechanism has been developed, and allows the reactions of N-tetrahydroisoquinolines (THIQs) with N-itaconimides to through four different pathways, including addition-cyclization, addition-elimination, addition-coupling, and addition-protonation, with satisfactory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 110 publications
(32 citation statements)
references
References 58 publications
1
31
0
Order By: Relevance
“…Upon further structural tuning, DPZ derivative 1 (Figure ), substituted with two 5‐methoxythienyl donors, was applied as photoredox catalyst in benchmark CDC reaction as well as in oxidation, oxidative hydroxylation, and reductive dehalogenation where showed outstanding catalytic activity . These encouraging results prompted us to investigate catalytic activity, substrate scope, and limits of 1 in further reactions including chemodivergent radical cascade reactions between N ‐tetrahydroisoquinolines and N ‐itaconimides, pH‐controlled photooxygenation of indoles, and enantioselective oxidative C(sp 3 )‐H olefinations . The oxygenation of indoles further proved capability of DPZ photoredox catalysts to undergo either PET or EnT pathways …”
Section: Introductionmentioning
confidence: 99%
“…Upon further structural tuning, DPZ derivative 1 (Figure ), substituted with two 5‐methoxythienyl donors, was applied as photoredox catalyst in benchmark CDC reaction as well as in oxidation, oxidative hydroxylation, and reductive dehalogenation where showed outstanding catalytic activity . These encouraging results prompted us to investigate catalytic activity, substrate scope, and limits of 1 in further reactions including chemodivergent radical cascade reactions between N ‐tetrahydroisoquinolines and N ‐itaconimides, pH‐controlled photooxygenation of indoles, and enantioselective oxidative C(sp 3 )‐H olefinations . The oxygenation of indoles further proved capability of DPZ photoredox catalysts to undergo either PET or EnT pathways …”
Section: Introductionmentioning
confidence: 99%
“…Under these reaction conditions,conversion was complete within 24 hours and the desired product 3aa was obtained with 83 %y ield, 8.8:1 d.r, and 99 % ee (entry 1). [10] Control experiments also revealed that photocatalyst, cobalt catalyst, and visible light were essential for the reaction (entries 19-21), as either no reaction or poor yield was observed in their absence. value,oree value.When m-NO 2 C 6 H 4 COOH was replaced by benzoic acid, the yield significantly decreased to 16 %with 17 %H 2 evolution (entry 15).…”
mentioning
confidence: 99%
“…(11‐3)], and addition–protonation [Eq. (11‐4)] pathways by modulation of the solvent, temperature, and additives . Under reaction conditions A, LiPF 6 acts as a Lewis acid cocatalyst and accelerates the nucleophilic addition of radical A to 51 to form intermediate B , which is further stabilized by LiPF 6 , which inhibits the oxidation of DPZ −.…”
Section: Sulfur‐containing Photosensitizersmentioning
confidence: 99%